2016
DOI: 10.1155/2016/8065736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Phytotoxic and Genotoxic Potential of Pulp and Paper Mill Effluent Using Vigna radiata and Allium cepa

Abstract: Pulp and paper mill effluent induced phytotoxicity and genotoxicity in mung bean (Vigna radiata L.) and root tip cells of onion (Allium cepa L.) were investigated. Physicochemical characteristics such as electrical conductivity (EC), biological oxygen demand (BOD 5 ), chemical oxygen demand (COD), and total phenols of the pulp and paper mill effluent were beyond the permissible limit specified for the discharge of effluent in inland water bodies. Compared to control plants, seedling exposed to 100% effluent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Stickiness is the indicator and also signifies high toxicity of dye which will lead to irreversibility of chromosomal aberrations and cell death (Alimba et al 2013). This result similar to the previous report, in which onion bulbs were exposed to pulp and paper mill effluent, induced chromosomal aberrations and nuclear abnormalities compared to the control bulbs (Haq et al 2016). This confirmed the interference of the chemicals presence in the dye, whereas the bulbs grown in treated dye solution did not show any inhibition effect on root elongation.…”
Section: Cytotoxicity Of the Treated And Untreated Bg Dyesupporting
confidence: 90%
See 1 more Smart Citation
“…Stickiness is the indicator and also signifies high toxicity of dye which will lead to irreversibility of chromosomal aberrations and cell death (Alimba et al 2013). This result similar to the previous report, in which onion bulbs were exposed to pulp and paper mill effluent, induced chromosomal aberrations and nuclear abnormalities compared to the control bulbs (Haq et al 2016). This confirmed the interference of the chemicals presence in the dye, whereas the bulbs grown in treated dye solution did not show any inhibition effect on root elongation.…”
Section: Cytotoxicity Of the Treated And Untreated Bg Dyesupporting
confidence: 90%
“…After washing, the root tips were cut and fixed in absolute alcohol and glaciel acetic acid (3:1) for 12 h (Haq et al 2016). After that, the root meristems were cut and stained with 0.5% acetocarmine for 5 min without hydrolysis.…”
Section: Collection and Preparation Of Onion Bulbsmentioning
confidence: 99%
“…Significant reduction in radicle length (75.37%) and plumule length (83.6%) was observed at 100% (v/v) wastewater and biomass of 25.49, 53.69, 61.90, 69.01, and 74.41% at 5, 10, 25, 50, and 100% (v/v), respectively as compared to control (Table 10). Haq et al (2016) found that diluted effluents (12.5-50%) had not affected V. radiata seed Table 6. Reversion of Salmonella tester strains in the presence of n-hexane extracted wastewater samples.…”
Section: Resultsmentioning
confidence: 96%
“…Seed germination assay was performed by the method of Haq et al (2016) with some modifications. Black gram seeds (Vigna mungo L.) were sterilized using 70% ethanol followed by 3% sodium hypochlorite solution (each for 3 min) and then washed with sterile double distilled water.…”
Section: Vigna Mungo Phytotoxicitymentioning
confidence: 99%
“…According to Pathiratne et al, the most frequent and easily recognizable chromosomal abnormality in the Allium cepa root meristematic cells was vagrant chromosomes [18]. Chromosomal adherence may occur due to the increased chromosomal contraction and condensation [23]. According to the Fiskesjo, presence of chromosomal adherence is considered as a common sign of toxic effects on chromosomes [24].…”
Section: Allium Cepa Bioassaymentioning
confidence: 99%